Mechanistic Insights into Superoxide Dismutation Driven by Dinuclear Manganese Complexes: The Role of the Mn2-Core - Squarcina, Andrea; Fehn, Dominik; Scheitler, Andreas; Senft, Laura; Franke, Alicja; Zahl, Achim; Puchta, Ralph; Meyer, Karsten; Ivanovic-Burmazovic, Ivana (ACS Catalysis, 2023)
The dinuclear Mn2(II,II)L2-core (HL = 2-[[di(2-pyridyl)methyl](methyl)amino]-methylphenol) has been recently reported to be the most active dual superoxide dismutase (SOD) and catalase (CAT) functional analogue, enabling cascade detoxification of the superoxide radical anion. Here, we investigated the mechanism of catalytic O2•– decomposition by two stereoisomers with the Mn2(II,II)L2-core, Mn2L2Ac and Mn2L2, in order to (i) precisely determine the catalytic SOD activity of the complexes, (ii) characterize the key intermediates involved in the dismutation process, and (iii) discriminate between single- and di-Mn center catalysis in relation to the configuration of the Mn2-core. The conclusions drawn from low-temperature mass spectrometry, stopped-flow kinetics, cyclic voltammetry, water exchange 17O nuclear magnetic resonance (NMR), and electron paramagnetic resonance (EPR) analyses were supported by the structural characterization and quantum chemical analysis of the proposed reaction intermediates. This study allows us to determine kcat for Mn2L2Ac and Mn2L2 (4.6 × 107 and 2.2 × 107 M–1 s–1, respectively, in 3-(N-morpholino)propanesulfonic acid (MOPS) at pH = 7.4) and detect the key intermediates involved in the catalytic cycle driven by these Mn2-SOD mimics, highlighting the formation of a side-on η2–Mn2(III,II)–peroxo, as an initial intermediate. The effects of the Mn2(II,II)-core configuration on the SOD activity were discussed.<br
CRIS-Team Scopus Importer:2023-07-28
Keywords: Dinuclear core; Kinetics; Manganese Catalysis; Peroxo intermediates; Stopped-flow; Superoxide Dismutases